OFFSET
2,2
LINKS
Albert Zhou, Proof of recurrence
FORMULA
From Albert Zhou, Jan 26 2025: (Start)
a(2*n) = a(2*(n-1)) + (n-1)*a(2*(n-2)) + 4*(n-1)*b(2*(n-1)) + 2*(n-1)*(n-2)*c(2*(n-1)), where
b(2*n) = 2*a(2*(n-1)) + 2*(n-1)*b(2*(n-1)), and
c(2*n) = 4*b(2*(n-1)) - 2*a(2*(n-2)) + 4*(n-2)*a(2*(n-3)) + 4*(n-2)*(n-3)*c(2*(n-2)), with
a(0) = 1, a(2) = 1, a(4) = 10, and
b(0) = 0, b(2) = 2, b(4) = 6, and
c(0) = 0, c(2) = 1, c(6) = 6.
a(2*n+1) = n*b(2*n).
Proof attached. (End)
PROG
(Python)
# Even-dim bisymmetric
A = [1, 1, 10]
B = [0, 2, 6]
C = [0, 1, 6]
for n in range(3, 13):
a_next = A[-1] + (n-1)*A[-2] + 4*(n-1)*B[-1] + 2*(n-1)*(n-2)*C[-1]
b_next = 2*A[-1] + 2*(n-1)*B[-1]
c_next = 4*B[-1] - 2*A[-2] + 4*(n-2)*A[-3] + 4*(n-2)*(n-3)*C[-2]
A.append(a_next)
B.append(b_next)
C.append(c_next)
# Odd-dim bisymmetric
A_odd = [B[n]*n for n in range(len(B))]
# Albert Zhou, Jan 26 2025
CROSSREFS
KEYWORD
nonn
AUTHOR
R. H. Hardin, Feb 09 2009
EXTENSIONS
a(26)-a(27) from Albert Zhou, Jan 26 2025
STATUS
approved